Comparison and analysis of the nucleotide sequences of pilin genes from Haemophilus influenzae type b strains Eagan and M43. - Forney, L J (1991)
Previous studies have demonstrated antigenic differences among the pili expressed by various strains of Haemophilus influenzae type b (Hib). In order to understand the molecular basis for these differences, the structural gene for pilin was cloned from Hib strain Eagan (p+) and the nucleotide sequence was compared to those of strains M43 (p+) and 770235 b0f+, which had been previously determined. The pilin gene of Hib strain Eagan (p+) had a 648-bp open reading frame that encoded a 20-amino-acid leader sequence followed by the 196 amino acids found in mature pilin. The translated sequence was three amino acids larger than pilins of strains M43 (p+) and 770235 b0f+ and was 78% identical and 95% homologous when conservative amino acid substitutions were considered. Differences between the amino acid sequences were not localized to any one region but rather were distributed throughout the proteins. Comparison of protein hydrophilicity profiles showed several hydrophilic regions with sequences that were conserved between strain Eagan (p+) and pilins of other Hib strains, and these regions represent potentially conserved antigenic domains. Southern blot analyses using an intragenic probe from the pilin gene of strain Eagan (p+) showed that the pilin gene was conserved among all type b and nontypeable strains of H. influenzae examined, and only a single copy was present in these strains. Homologous genes were not present in the phylogenetically related species Pasteurella multocida, Pasteurella haemolytica, and Actinobacillus pleuropneumoniae. These data indicate that the pilin gene was highly conserved among different strains of H. influenzae and that small differences in the pilin amino acid sequences account for the observed antigenic differences of assembled pili from these strains.